ANALISIS KOMUNIKASI PERSUASIF CHANNEL YOUTUBE â€œKEMBAR MUSIC DIGITALâ€ UNTUK MENARIK MINAT PENONTON GENERASI Z PADA MUSIK CAMPURSAR - Anto, Dwi; Hindra H, Nurnawati; Itasari, Andri Astuti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACTThe interest of Generation Z viewers in Campursari music on the Kembar Music Digital YouTube channel is examined through persuasive communication techniques, linked to the number of viewers, likes, subscribers, and comments, which are predominantly contributed by Generation Z. This can be observed from the profile of viewers' accounts on each post on the Kembar Music Digital YouTube channel. This study was conducted to analyze persuasive communication in attracting the interest of Generation Z viewers. The theory applied in this research is Efendy's persuasive communication theory. This research is descriptive in nature with a qualitative method. The results show that Generation Z's interest in Campursari music on the Kembar Music Digital YouTube channel is influenced by music arrangement, song selection, singer choice, and video quality in each post. This is supported by interviews with informants, who are subscribers and viewers of Kembar Music Digital, confirmed to be interested in Campursari music on the channel and considered reliable as data sources for the research.Keywords: Kembar Music Digital, Persuasive Communication, Generation Z Viewers Interest